2007
DOI: 10.1111/j.1468-3148.2007.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Mental Health Services by People with Intellectual Disabilities

Abstract: Background Although research is starting to identify those factors that predict contact with mental health services in individuals with intellectual disabilities, very little is known about the patterns of service use following referral. Yet, this information is vital for effective service planning and development. We therefore examined the factors associated with service consumption. Methods We constructed a service consumption index based on the number of outpatient clinics attended, contacts with the commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…The same pattern has been found among people with ID with referrals to a community based mental health service in the UK [45]. This skewness in the distribution of registrations could suggest the presence of a group of people with ID and severe, or complex, psychiatric co-existing disorders.…”
Section: Discussionsupporting
confidence: 62%
“…The same pattern has been found among people with ID with referrals to a community based mental health service in the UK [45]. This skewness in the distribution of registrations could suggest the presence of a group of people with ID and severe, or complex, psychiatric co-existing disorders.…”
Section: Discussionsupporting
confidence: 62%
“…In Canada, the responsibility for the provision of health services was transferred from the institution to general community-based services in the 1970s . However, research has shown that these community-based services are unable to adequately deal with the concerns of individuals with ID and their family caregivers, particularly in regard to mental health issues (Lunsky, Garcin, Morin, Cobigo, & Bradley, 2007;Spiller et al, 2007;Ziring et al, 1988). Past research in Canada has found individuals with ID to be disproportionately high users of mental health services, with mental health issues accounting for the majority of hospitalizations in this population (Balogh, Hunter, & Ouellette-Kuntz, 2005;Lunsky & Balogh, 2010) and emergency department (ED) use occurring more than twice as frequently in those with a psychiatric disorder and ID as in those with a psychiatric disorder without ID (Lunsky et al, 2011).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Few studies have investigated the nature of service utilization by adults with intellectual disabilities (Spiller et al . ), especially in relation to specialist community‐based health services and for the management of aggressive behaviour (Jacobsen ; Hemmings ). Similarly, few studies are currently available to assess the economic impact of various forms of psychosocial, environmental and medication‐based interventions for aggressive behaviour in adults with intellectual disabilities.…”
Section: Introductionmentioning
confidence: 99%